An Iot-Based Method for Managing Power Grids in Smart Way - Gündüç, Semra; Gaeed, Saif Ali (International Journal of Intelligent Systems and Applications in Engineering, 2022)
System designers find it difficult to reduce power consumption. High power consumption leads to higher temperatures, affecting performance and reliability. Increasing energy prices and concerns regarding the impact of electronic systems on the environment highlight the importance of low power consumption. Smart grids are emerging as a new side of the power industry. They incorporate advanced technologies and solve many problems, but continue to face readiness challenges. A new technology called the Internet of Things (IoT) is making it possible to monitor and manage electricity consumption, wherever a variety of different technologies are utilized, including IoT cloud platforms. In this research, smart grid and IoT technologies are used to build a power management system. It is also discussed how the system functions and is automated. Through the design of a system that detects voltage, current, and weather conditions and gathers data to warn consumers in advance of power usage problems, A system is proposed to monitor power consumption by consumers and control power usage by electrical devices. According to the data, it is possible to enhance the system in the future according to the region in which it is located, and reduce loads by preparing the system accordingly.